QUALITY OF LIFE AMONG TUBERCULOSIS PATIENTS WITH AND WITHOUT DIABETES MELLITUS BEFORE AND AFTER ANTI-TB DRUGS ADMINISTRATION - Ksatriaputra, Alesandro; Kholis, Fathur Nur; Ngestiningsih, Dwi; Hariyana, Bambang (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background : Increased TB prevalence with and without diabetes mellitus affects the quality of life of the patients. Appropriate action on TB patients was needed in health status improvement and quality of life of the patients. SF-36 questionnaire as an instrument to assess the quality of life. Aim : To compare Quality of Life (QoL) between TB with diabetes mellitus patients and TB without diabetes mellitus patients before and after the treatment of tuberculosis. Methods : A cross-sectional design was performed in this study by collecting data from the medical record of patients in Kariadi Hospital Semarang who were diagnosed with tuberculosis. Research subjects were 44 people with 22 TB with diabetes mellitus patients and 22 TB without diabetes mellitus patients. The direct approach was carried out using the SF-36 questionnaire. The SF-36 questionnaire was filled out using telephone interview. All questions were scored on a scale from 0 to 100, with 100 represents the highest level of function with interpretation the higher the score the higher the level of function, and vice versa. Statistical tests use Wilcoxon Test and Independent Samples T test. Results : Wilcoxon test on quality of life of TB patients with and without diabetes mellitus before and after treatment of tuberculosis was significant (p = 0.0040). Mean improvement in quality of life difference before and after treatment of tuberculosis in TB without diabetes mellitus patients (p = 41.72) was more significant than TB with diabetes mellitus patients (p = 26.38). Conclusion : There was a significant difference in quality of life between TB with and without diabetes mellitus patients before and after the treatment of tuberculosis as indicated by the SF-36 questionnaire score. TB without diabetes mellitus patients have more significant changes in quality of life compared to TB with diabetes mellitus patients.